Multiply to simplify the polynomial expression (r - 1)(r ^ 2 - 2r + 3) 2 points

1 answer

To simplify the polynomial expression \((r - 1)(r^2 - 2r + 3)\), we can use the distributive property (also known as the FOIL method for binomials):

  1. Distribute \(r\) from the first expression to each term in the second expression: \[ r \cdot r^2 = r^3 \] \[ r \cdot (-2r) = -2r^2 \] \[ r \cdot 3 = 3r \]

  2. Next, distribute \(-1\) from the first expression to each term in the second expression: \[ -1 \cdot r^2 = -r^2 \] \[ -1 \cdot (-2r) = 2r \] \[ -1 \cdot 3 = -3 \]

Now we combine all these results: \[ r^3 - 2r^2 + 3r - r^2 + 2r - 3 \]

Next, combine like terms:

  • The \(r^2\) terms: \(-2r^2 - r^2 = -3r^2\)
  • The \(r\) terms: \(3r + 2r = 5r\)

Putting it all together, we have: \[ r^3 - 3r^2 + 5r - 3 \]

Thus, the simplified polynomial expression is: \[ \boxed{r^3 - 3r^2 + 5r - 3} \]